2003
DOI: 10.1095/biolreprod.102.003590
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Messenger RNA for Prostaglandin E Receptor Subtypes EP4/EP2 and Cyclooxygenase Isozymes in Mouse Periovulatory Follicles and Oviducts During Superovulation1

Abstract: Prostaglandin (PG) E(2) is synthesized from arachidonic acid by cyclooxygenase (COX) and acts as a regulator in ovulation and fertilization reactions. We present the temporal and regional expression patterns of mRNAs for the two Gs-coupled PGE receptors, EP2 and EP4, and for COX-1 and COX-2 in mouse periovulatory follicles and oviducts during superovulation. Analysis using reverse transcription polymerase chain reaction revealed that the mouse ovaries express a significant amount of EP4 mRNA in addition to EP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 31 publications
4
52
0
2
Order By: Relevance
“…By contrast, higher PTGS2 mRNA levels occur in the cumulus cells of human oocytes expressing the highest developmental capacity (Gebhardt et al 2011). In cat COCs, we indeed observed increased PTGS2 mRNA expression after oocyte maturation in situ, which was consistent with earlier observations in the pig (Kawashima et al 2008) and mouse (Segi et al 2003). Nonetheless, the level of induction of PTGS2 transcription (post-eCG/hCG in intact cats) did not vary between seasons despite being clear compromises in oocyte developmental potential during both simulated and natural reproductively quiescent (compared to active) periods.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, higher PTGS2 mRNA levels occur in the cumulus cells of human oocytes expressing the highest developmental capacity (Gebhardt et al 2011). In cat COCs, we indeed observed increased PTGS2 mRNA expression after oocyte maturation in situ, which was consistent with earlier observations in the pig (Kawashima et al 2008) and mouse (Segi et al 2003). Nonetheless, the level of induction of PTGS2 transcription (post-eCG/hCG in intact cats) did not vary between seasons despite being clear compromises in oocyte developmental potential during both simulated and natural reproductively quiescent (compared to active) periods.…”
Section: Discussionsupporting
confidence: 91%
“…Second, these processes are attenuated by a mixed EP2/EP4 antagonist. Third, EP2, EP3, and EP4 are expressed in cumulus cells, and hCG up-regulates EP2 and EP4 expression in these cells (28). However, the role of EP3 in cumulus cell function does not appear to be critical, because EP3 null females do not exhibit overt reproductive phenotypes (11).…”
Section: Discussionmentioning
confidence: 99%
“…Vitro-Previous studies have demonstrated a spatiotemporal expression of COX-2 in mural granulosa and cumulus cells in response to preovulatory gonadotropin stimulation in mice (24,27,28). To further elucidate the physiological significance of COX-2-derived PGs in oocyte maturation in vitro, we first assessed COX-2 expression by immunofluorescence in wild-type COCs in culture.…”
Section: Pge 2 Differentially Regulates Oocyte Maturation and Cumulusmentioning
confidence: 99%
“…Ptgs2 is a crucial factor for ovulation and is generally induced around 3-h post-hCG (Lim et al 1997, Joyce et al 2001, Segi et al 2003. As shown in Fig.…”
Section: Resultsmentioning
confidence: 97%